Teori Bourdieu, Modal Budaya, dan Sastra Digital: Sintesis Teoretis dan Implikasi Penelitian - susanto, susanto (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
This study aims to synthesize the relevance of Pierre Bourdieu’s theory—particularly the concepts of habitus, cultural capital, and field—in the context of digital literature. Technological transformation has created a new arena where literary works are not only produced, distributed, and consumed through print media but also via digital platforms. This study employs a narrative literature review approach by examining articles, books, and recent research on the intersection of Bourdieu’s theory and digital phenomena. The synthesis shows that the concept of cultural capital remains relevant, but it requires an extension toward digital capital, which includes technological literacy, the ability to manage algorithms, and the capacity to build reader networks. Moreover, the literary habitus of the digital generation is shaped by interactions with online platforms that foster instant consumption, serialized narratives, and interactive participation. The concept of field is useful in mapping new dynamics of power in digital literature, where cultural authority is no longer monopolized by traditional institutions but also shaped by algorithms and virtual communities. This study concludes that applying Bourdieu’s theory to digital literature research requires an interdisciplinary approach that combines qualitative, quantitative, and digital ethnographic methods. The findings imply a more comprehensive methodological framework for literary research and a deeper understanding of capital distribution, cultural value production, and the democratization of literature in the digital era.